Recovery after a running training session: influence of exercise characteristics, hot-water immersion, and cold-water immersion - Dutra, Yago Medeiros [UNESP] (2025)
Running is one of the most widely used efforts in conditioning routines, however, the characteristics and time-course of fatigue after running at different intensities and/or types of execution (i.e., continuous or interval) have not yet been described. Moreover, fatigue is known to be task-dependent, whereby its characteristics and causal mechanisms will be influenced by aspects of exercise. In this way, due to discrepancies in basic mechanisms of action between cold-water immersion (CWI) and hot-water immersion (HWI), it is possible that their effectiveness in optimizing recovery after running may be influenced by aspects of the exercise performed and the characteristics of the fatigue established. Accordingly, the overall aim of this thesis was to investigate the influence of aspects of exercise, CWI and HWI on the fatigue-recovery continuum after running. To achieve this aim, a methodological study and three experimental studies were carried out. From the data gathered, we observed that: i) neuromuscular function assessment protocol involving maximal voluntary isometric contractions of the knee extensors, peripheral stimulation and monitoring of electromyography activity provides outcomes with a coefficient of variation <10% and repeatability <25% within day and between days; ii) even with equalized volume, peripheral fatigue and perceived fatigability are more pronounced after high-intensity interval exercise performed 50% above the velocity associated with the respiratory compensation point (vRCP; HIIT150%RCP) compared to exercise performed continuously at the velocity associated with vRCP (CONT100%RCP); however, central fatigue was greater after CONT100%RCP compared to HIIT150%RCP; iii) regardless of the characteristics of the effort, running 8-km causes impairments on neuromuscular function, cardiac parasympathetic activity, mood, cognitive function and greater physiological/psychological stress in successive brief effort for at least 6 hours after exercise; however, HIIT150%RCP caused greater impairment in dynamic neuromuscular function and greater perceived fatigability during successive brief efforts compared to CONT100%RCP, while high-intensity interval exercise performed 30% above vRCP (HIIT130%RCP) caused greater reduction in resting cardiac parasympathetic activity compared to CONT100%RCP; iv) both CWI and HWI were able to mitigate central fatigue after running compared to placebo and passive rest, but CWI only had this ability after HIIT150%RCP, while HWI only had this ability after CONT100%RCP; neither method mitigate the impairments in maximal voluntary isometric force production or tissue contractility of knee extensors; however, after both HIIT150%RCP and CONT100%RCP, CWI was able to increase resting cardiac parasympathetic activity and HWI was able to decrease cardiorespiratory demand during successive brief efforts compared to placebo and passive rest. In view of the data obtained, it was concluded that the intensity/type of running has an impact on the characteristics of fatigue and that the CWI and HWI for optimize recovery should be used taking into account the characteristics of the running performed and the recovery metric to be improved.